The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s2176-94512012000200016
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular disorders and parafunctional oral habits: an anamnestic study

Abstract: Objective: To assess the frequency and severity of the signs and symptoms of temporomandibular disorders (TMD), the frequency of parafunctional oral habits and the correlation between the variables by means of the patients' perception regarding their problem. Methods:One hundred patients diagnosed with TMD, through a clinical examination of their masticatory system, answered the questions of a previously published protocol concerning the signs and symptoms most frequently reported in the literature.Results: Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 28 publications
1
18
0
4
Order By: Relevance
“…Moreover, some studies have reported that the amount, frequency, intensity and duration of habits can determine the severity of signs and symptoms of TMD. 10 The prevalence of oral parafunctions in children ranges from 7% to 15.1%, 11 with girls reporting higher frequencies. 12 Frequently encountered oral parafunctions in children are bruxism, nail biting and non-nutritive sucking, 13 and the persistence of these activities might have detrimental effects on the oro-facial structures.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some studies have reported that the amount, frequency, intensity and duration of habits can determine the severity of signs and symptoms of TMD. 10 The prevalence of oral parafunctions in children ranges from 7% to 15.1%, 11 with girls reporting higher frequencies. 12 Frequently encountered oral parafunctions in children are bruxism, nail biting and non-nutritive sucking, 13 and the persistence of these activities might have detrimental effects on the oro-facial structures.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…It is believed that oral habits can be considered as an important aetiologic factor of temporomandibular disorders (TMD), as they lead to a traumatic dental occlusion that may affect the teeth and the masticatory muscles and temporomandibular joints, causing the disruption of the functional balance of the stomatognathic system, or worsening the already present TMD. Moreover, some studies have reported that the amount, frequency, intensity and duration of habits can determine the severity of signs and symptoms of TMD . The prevalence of oral parafunctions in children ranges from 7% to 15.1%, with girls reporting higher frequencies .…”
Section: Introductionmentioning
confidence: 99%
“…Segundo a literatura, a DTM é uma patologia comum, cujos sinais e sintomas clínicos e subclínicos chegam a afetar em torno de 50% da população geral, sendo mais prevalente em mulheres, entre as idades de 20 e 40 anos (Cordeiro & Guimarães, 2012;Dugashvili et al, 2013;Oliveira et al, 2012). Os estudos demonstram que a DTM está relacionada a fatores psicológicos, emocionais, fi siopatológicos e comportamentais (Melchior et al, 2012;Sydney & Conti, 2011). No entanto, não existe consenso entre os pesquisadores acerca da etiologia exata da DTM.…”
Section: Disfunción Temporomandibular: Síntomas De Ansiedad Depresióunclassified
“…A intensidade da dor referida pelos indivíduos com DTM e mensurada com base em uma escala de autorrelato constatou média total de 5,75 pontos, de acordo com a Tabela 2. Dessa forma, verifi ca-se que a intensidade da dor apresentou-se em nível moderado, o que pode estar relacionado à procura por atendimento odontológico (Conti et al, 2012;Melchior et al, 2012;Oliveira et al, 2012;Rollman et al, 2013). O período de tempo em que os 20 pacientes com DTM manifestaram dor variou de 12 a 240 meses; no entanto, a média permaneceu em 87 meses.…”
unclassified
See 1 more Smart Citation